Synthesis and characterization of pyrochlore lead zinc niobate nanopowders derived from Zn3Nb2O8 precursor - Phakkhananan Pakawanit (2018)
A novel approach to synthesis cubic pyrochlore lead zinc niobate-based Pb1.88Zn0.3Nb1.25O5.305 nanopowders with a modified mixed-oxide method has been developed. To ensure a pure phase pyrochlore formation, an intermediate phase of Zn3Nb 2O8 was employed as key precursor. The formation of pyrochlore phase in the calcined lead zinc niobate powders has been examined as a function of firing temperature by a combination of TG-DTA and XRD techniques. The morphology evolution has been examined by SEM technique. It has been found that the unreacted PbO and Zn3Nb2O8 phases tend to form together with lead zinc niobate, with the latter appearing in cubic phase. It is seen that optimization of firing temperature can lead to a single-phase Pb1.88Zn0.3Nb1.25O5.305 powders with average particle sizes ranging from 75-400 nm. © (2011) Trans Tech Publications.